2018
DOI: 10.1101/394346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boreal marine fauna from the Barents Sea disperse to Arctic Northeast Greenland

Abstract: All rights reserved. No reuse allowed without permission.(which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Christiansen et al (2016) showed that Atlantic cod, beaked redfish ( Sebastes mentella ) and capelin distributions should already be expected further north than what had previously been reported and argued that input from the warmer Barents Sea may have been a factor in explaining the newly established species in Northeast Greenland. Andrews et al (2019) used genetic methods to confirm the boreal input to the Northeast Greenland fish fauna as coming from the Barents sea, by genotyping specimens of Atlantic cod, beaked redfish and northern shrimp and assigning them to ancestral populations. They further argued that given the juvenile stages of the fishes caught, the most likely explanation for the dispersal route was the dispersal of pelagic offspring via advection across the Fram Strait from the Barents Sea to Northeast Greenland.…”
Section: Discussionmentioning
confidence: 99%
“…Christiansen et al (2016) showed that Atlantic cod, beaked redfish ( Sebastes mentella ) and capelin distributions should already be expected further north than what had previously been reported and argued that input from the warmer Barents Sea may have been a factor in explaining the newly established species in Northeast Greenland. Andrews et al (2019) used genetic methods to confirm the boreal input to the Northeast Greenland fish fauna as coming from the Barents sea, by genotyping specimens of Atlantic cod, beaked redfish and northern shrimp and assigning them to ancestral populations. They further argued that given the juvenile stages of the fishes caught, the most likely explanation for the dispersal route was the dispersal of pelagic offspring via advection across the Fram Strait from the Barents Sea to Northeast Greenland.…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in species distributions are already appearing faster than projected by current models, and the resulting mixing of species of differing biogeographic origins may lead to new evolutionary pressures and adaptations (50). Changes in the environment will not only alter the distribution patterns of native species but also open routes for invasive ones (54), with potentially large impacts on native biota and ecosystem services (e.g., seafood production).…”
Section: Biological Consequences Of the Changing Oceanmentioning
confidence: 99%
“…This is of relevance in the context of ongoing anthropogenic climate change, which is expected to be particularly severe in Arctic regions (Leduc et al, 2016). Here, cold adapted Arctic species will have limited possibilities for migrating to cooler environments and may experience increased competition and predation from boreal species (e.g., Andrews et al, 2019; Renaud et al, 2012). Consideration of phylogeographical patterns in Arctic species is therefore important for demarcating major units for conservation and for identifying possible secondary contact between divergent lineages that could increase standing genetic variation, and thus potential for adapting to altered temperature regimes.…”
Section: Introductionmentioning
confidence: 99%